Anionic Lipids: A Pipeline Connecting Key Players of Plant Cell Division - Caillaud, Marie-Cécile (Frontiers in Plant Science, 2019)
How cells position their division plane is a critical component of cell division. Indeed, it defines whether the two daughter cells divide symmetrically (with equal volumes) or not, and as such is critical for cell differentiation and lineage specification across eukaryotes. However, oriented cell divisions are of special significance for organisms with cell walls, such as plants, because their cells are embedded and cannot relocate. Correctly positioning the division plane is therefore of prevailing importance in plants, as it controls not only the occurrence of asymmetric cell division, but also tissue morphogenesis and organ integrity. While cytokinesis is executed in radically different manners in animals and plants, they both rely on the dynamic interplay between the cytoskeleton and membrane trafficking to precisely deliver molecular components to the future site of cell division. Recent research has shown that strict regulation of the levels and distribution of anionic lipids, which are minor components of the cell membrane’s lipids, is required for successful cytokinesis in non-plant organisms. This review focused on the recent evidence pointing to whether such signaling lipids have roles in plant cell division.